Marine Lipids and the Bioavailability of Omega-3 Fatty Acids - Mu, Huiling; Mullertz, Anette (Current Nutrition & Food Science, 2015)
Marine lipids are enriched with omega-3 fatty acids, especially eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). Omega-3 fatty acids are important membrane lipids and have many recognized health benefits, the bioavailability of these fatty acids can therefore be important for achieving the beneficial healthy effects. As important membrane lipids, the incorporation and depletion kinetics of EPA and DHA in biological membranes have been found to be different, DHA was depleted slowly from both erythrocyte and plasma membranes due to the slow re-synthesis of DHA in the body. The bioavailability of omega-3 fatty acids has been reported to be affected by several factors; among the important factors were the digestion and absorption processes of omega-3 containing lipids in the gastrointestinal tract. Both lipid structures and food structures can affect the bioavailability of omega-3 fatty acids. Human studies have shown that the relative bioavailability of omega-3 fatty acids from fish oil (triglyceride formulation) was similar to that from fish, whereas lower relative bioavailability was observed from fatty acid ethyl ester (FAEE) formulation in comparison with other lipid formulations. In vitro studies provided a mechanistic understanding on the varied bioavailability caused by different lipid structures, the lower relative bioavailability of omega-3 fatty acids from FAEE formulation was closely related to the slower digestion rate of FAEE. Microencapsulated fish oil has often been used as a food additive because of its better chemical stability; studies showed that microencapsulation did not affect the bioavailability significantly. Even though food structures also affect the digestion and absorption of omega-3 containing lipids, several studies have shown that long-term intake of fish oil and food products enriched with fish oil is an efficient way to provide EPA and DHA.
Keywords: DHA